A new approach to solving production-appropriation games with many heterogeneous players - Richard Cornes; Roger Hartley; Yuji Tamura (Center for Economic Studies and ifo Institute (CESifo), 2010)
We set out a model of production and appropriation involving many players, who differ with respect to both resource endowments and productivities. We write down the model in a novel way that permits our analysis to avoid the proliferation of dimensions associated with the best response function approach as the number of heterogeneous players increases. We establish existence of a unique equilibrium in pure strategies, and carry out some comparative static exercises.
Keywords: C72; D74; 330; conflict; noncooperative games; aggregative games; Konflikt; Nichtkooperatives Spiel; Gleichgewicht; Theorie